Mechanism of biosorption of Pb (ii) and Cu (ii) ions using dead biomass of Fusarium equiseti strain UMAS and Penicillium citrinum strain UMAS B2 - Akinkunmi, Wahab Abideen; Husaini, Awang Ahmad Sallehin Awang; Zulkharnain, Azham; Tay, Meng Guan; Roslan, Hairul Azman (Journal of Biochemistry, Microbiology and Biotechnology, 2016)
Filamentous fungi such as Fusarium equiseti KR706303 and Penicillium citrinum KR706304 are capable of sequestering heavy metals from aqueous solutions. In the present study, the role play by various functional groups present in the cell wall of F. equiseti KR706303 and P. citrinum KR706304 during lead and copper ions biosorption was investigated. The fungal biomass was chemically treated to modify the functional groups present in their cell wall. These modifications were studied through biosorption experiments. It was found that an esterification of the carboxyl and phosphate groups, methylation of the amine groups and extraction of lipids significantly decrease the biosorption of both lead and copper ions studied. Therefore, the carbonyl, hydroxyl and amide groups were recognized as important in the biosorption of metal ions by the tested fungi. The study showed that there was no release of any metal ions from the biomass after biosorption, indicating that ion exchange may not be a key mechanism in the biosorption of lead and copper ions by these fungi but complexation of metal ions within the fungal cell wall.